PENERAPAN INTERVENSI RENDAM PERMANGANAS KALIUS (PK) TERHADAP PENURUNAN NYERI PADA PASIEN POST OP HEMOROIDEKTOMY - Nurwidiasih; Setiyowati, Yovita Dwi (Yayasan Healing and Healthcare Education, 2025)
Post-hemorrhoidectomy pain is a common complication that may impede the recovery process. Non-pharmacological interventions such as potassium permanganate (KMnO₄) sitz baths have shown potential in pain management and wound healing. This case study aims to evaluate the effectiveness of KMnO₄ sitz bath therapy in reducing post-hemorrhoidectomy pain. A 45-year-old male patient (Mr. A) experienced severe postoperative pain (7/10 on the Numerical Rating Scale). Sitz baths with a 0.1–0.2% KMnO₄ solution were administered twice daily. Pain intensity was measured before and after each intervention using the NRS. Within 2–3 days, the patient’s pain level decreased significantly to 3/10, accompanied by improved comfort, enhanced mobility, and positive behavioral responses. The analgesic effects are associated with the antiseptic and astringent properties of KMnO₄, as well as the muscle-relaxing effects of warm water, which together reduce inflammation, prevent infection, and alleviate anal sphincter spasms. These findings support the use of potassium permanganate sitz baths as an effective non-pharmacological intervention in managing post-hemorrhoidectomy pain and promoting recovery.